AN ANALYSIS OF SPEECH ACT IN THE ‘ONE PIECE’ LIVE ACTION TV SERIES - Muhammad Ramdani; Elli Marliana (GLOBAL: Education Language and Humanity Journal, 2024)
This study focuses on the commissive speech acts used by the main character in the live-action TV series ‘One Piece’. The aim of this research is to identify the types and uses of commissive speech acts employed by the main character. Specifically, the study seeks to describe (1) the types and uses of commissive speech acts by the main character in the first episode of the One Piece live-action TV series. This research is qualitative in nature, using two instruments for data collection: observation and documentation. Based on the data obtained, it was found that the main character used a total of forty-five commissive speech acts, categorized into six types: promises (fourteen utterances), threats (five utterances), guarantees (five utterances), volunteering (six utterances), offers (seven utterances), and refusals (eight utterances). Additionally, the researchers found pedagogical significance in these findings.